IMPLEMENTASI HILIRISASI MINERAL DAN BATU BARA DALAM RANGKA MEWUJUDKAN KEDAULATAN ENERGI DAN DAYA SAING INDUSTRI NASIONAL - Rio Fafen Ciptaswara; Sulistiowati (Mimbar Hukum, 2022)
Abstract This research is aimed at identifying the obstacles of coal and mineral downstreaming implementation in Indonesia, as well as policy formulations that could be drawn up so that the implementation of downstreaming can realize energy sovereignty and increase the competitiveness of the national industry. The research method is sociological juridical research by analyzing the gap between the law (Das Sollen) and the implementation that being carried out in the field (Das Sein), and analyzed by using comparative descriptive with a qualitative approach, where the collected data comes from related regulations regarding mineral and coal resources management as well as the obligation to implement mineral and coal downstreaming in Indonesia, as well as regulations and policies for the management of mineral and coal resources in other countries that have characteristics related to Indonesia. The results of the study reveal that the obstacles of coal and mineral downstreaming implementation are resulted from the potential occurrence of resource curse; the existence political intervention; inconsistencies of policies to achieve energy sovereignty, and synergy challenge on national mining industry and manufacture industry. In order to formulate the downstreaming policy, it shall address and encourage the development of an Integrated Mineral and Coal Based Industry as well as the strengthening of the role of SOEs in the implementation of mineral and coal downstreaming. Abstrak Penelitian ini ditujukan untuk mengidenfikasi hambatan yang timbul dalam pelaksanaan hilirisasi atas mineral dan batu bara di Indonesia, serta formulasi kebijakan yang dapat disusun agar pelaksanaan hilirisasi dapat mewujudkan kedaulatan energi dan peningkatan daya saing industri nasional. Metode penelitian yang digunakan adalah penelitian yuridis sosiologis dengan melihat kesenjangan antara hukum yang dikehendaki (das sollen) dengan implementasi yang terlaksana di lapangan (das sein), serta dilakukan analisa secara deskriptif komparatif dengan pendekatan kualitatif, dimana data yang dikumpulkan bersumber dari peraturan-peraturan terkait dengan pengelolaan sumber daya mineral dan batu bara serta kewajiban pelaksanaan hilirisasi mineral dan batu bara di Indonesia, serta peraturan dan kebijakan pengelolaan sumber daya mineral dan batu bara di negara lain yang memiliki karakteristik yang terkait dengan Indonesia. Hasil penelitian mengungkapkan bahwa hambatan pelaksanaan hilirisasi mineral dan batu bara di Indonesia diantaranya berasal dari adanya potensi timbulnya resource curse; adanya political intervention; serta inkonsistensi kebijakan dalam pencapaian kedaulatan energi dan tidak sinerginya industri pertambangan dengan industri manufaktur nasional. Dalam menyusun formulasi kebijakan yang disusun, haruslah mendorong adanya pembangunan Integrated Mineral and Coal Based Industry serta adanya penguatan peran BUMN dalam pelaksanaan hilirasi mineral dan batu bara.